2001
DOI: 10.1002/mrm.1086
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of respiration‐induced noise fluctuations from undersampled multislice fMRI data†

Abstract: Functional MRI time series data are known to be contaminated by highly structured noise due to physiological fluctuations. Significant components of this noise are at frequencies greater than those critically sampled in standard multislice imaging protocols and are therefore aliased into the activation spectrum, compromising the estimation of functional activations and the determination of their significance. However, in this work it is demonstrated that unaliased noise information is available in multislice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 9 publications
0
72
0
Order By: Relevance
“…The aforementioned studies suggest variations in breathing pattern that are correlated with the stimulus presentation can lead to activation artefact, and ultimately compromise accurate detection of regions truly activated by the task of interest. If any phase of the respiratory cycle (inspiration or expiration) is task-correlated, it could result in activation artefact since the fMRI signal fluctuates with respiration [3,12]. Given that exercise and speech tasks can be associated with head motion and alterations to regular breathing they present a challenge in fMRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned studies suggest variations in breathing pattern that are correlated with the stimulus presentation can lead to activation artefact, and ultimately compromise accurate detection of regions truly activated by the task of interest. If any phase of the respiratory cycle (inspiration or expiration) is task-correlated, it could result in activation artefact since the fMRI signal fluctuates with respiration [3,12]. Given that exercise and speech tasks can be associated with head motion and alterations to regular breathing they present a challenge in fMRI.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated and tried to accommodate for MRI signal fluctuation with respiration [3,[11][12][13]. Bulk susceptibility or air volume variation in the lungs correlates with variations in the static magnetic field and is a significant source of respiratory noise [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…These measurements do not examine blood parameters directly, and are at best an indirect measure of the corresponding cerebral blood changes that affect fMRI signals, due to the complicated hemodynamic responses that affect both the shapes and delays in the BOLD waveform. Some studies have concentrated on using shorter repetition time (TR) (500 milliseconds) to avoid the aliasing problem altogether (Frank et al, 2001), but this requires a significant reduction in the spatial resolution or extent of brain coverage of the fMRI data.…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off window must be chosen carefully to avoid removing signals of interest together with the noise. In addition, there are now methods to attempt to correct physiological noise at source, such as the retrospective correction of physiological motion effects in fMRI (RETROICOR) (Glover et al, 2000;Frank et al, 2001).…”
Section: Discussionmentioning
confidence: 99%